A Happy Choice: Wellbeing as the Goal of Government - Paul Frijters; Andrew E. Clark; Christian Krekel; Richard Layard (Institute of Labor Economics (IZA), 2019)
In this article, we lay out the basic case for wellbeing as the goal of government. We briefly review the history of this idea, which goes back to the ancient Greeks and was the acknowledged ideal of the Enlightenment. We then discuss possible measures on which a wellbeing orientation could be based, emphasising the importance of acknowledging the political agency of citizens and thus their own evaluations of their life. We then turn to practicalities and consequences: how would one actually set up wellbeing-oriented decision-making and what difference should we expect from current practice? We end by discussing the current barriers to the adoption of wellbeing as the goal of government, both in terms of what we need to know more about and where the ideological barriers lay.
Keywords: I3; A10; H10; H83; 330; subjective wellbeing; life satisfaction; public policy; political economy; social welfare